2022
DOI: 10.3389/fmars.2022.806847
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic and Spatiotemporal Changes in Isotopic Niche of Jumbo Squid (Dosidicus gigas) in the Southeastern Pacific

Abstract: Jumbo squid (Dosidicus gigas) plays an important role in food webs throughout the eastern Pacific; however, its trophic ecology is complex, because it is a highly migratory and opportunistic predator. In this study, δ13C and δ15N values were measured along the lateral wall of lower beak to investigate the ontogenetic and spatiotemporal feeding strategy shifts of jumbo squid, respectively. Both year and area had significant influences on δ13C (p < 0.01), while sex and stage had no significant influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
0
3
1
Order By: Relevance
“…This means that high individual variation in habitat usage and different migratory capabilities between sexes are not enough to differentiate niches between females and males due to individual squid’s highly generalist diets. These results contrast with previous studies on other cephalopods where significant differences in niche width were found between sexes [ 30 , 49 , 123 , 125 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This means that high individual variation in habitat usage and different migratory capabilities between sexes are not enough to differentiate niches between females and males due to individual squid’s highly generalist diets. These results contrast with previous studies on other cephalopods where significant differences in niche width were found between sexes [ 30 , 49 , 123 , 125 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This is the first application of s to stable isotopic data from marine invertebrates to the authors’ knowledge. Specialization index s of δ 15 N shows that G. fabricii is a generalist predator, as most predatory squids are e.g., [ 48 , 50 , 120 , 121 , 122 , 123 ]. Significant differences in s of δ 15 N between the sexes in G. fabricii are influenced by only one individual: s values were 0.95–0.98 in all individuals, except female F5 with s = 0.83.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Containing continuous growth increments, these structures have been used in age and growth studies of squid (Arkhipkin et al 2018), and have also been used to obtain a chronological record of feeding ecology using stable isotope analysis, e.g. gladius (Kato et al 2016), beak (Hu et al 2022), eye lens (Meath et al 2019, Liu et al 2020).…”
Section: Introductionmentioning
confidence: 99%